Drying to preserve - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Drying is an old and well-established method of food preservation. Traditionally, crops (and fish) are spread out in the sun to dry, but this leaves them vulnerable to the vagaries of the weather to attack by pests and theft by birds and animals....